Odwołania do kultury literackiej narodów słowiańskich podczas pielgrzymek Jana Pawła II do krajów Europy Środkowej (Bułgaria, Chorwacja, Cz echosłowacja, Słowacja, Słowenia) = References to the literary culture of the Slavic countries visited by John Paul II during his pilgrimages to Central Europe (Bulgaria, Croatia, Czechoslovakia, Slovakia, Slovenia) - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article introduces authors and their works that the pope spoke about while visiting countries of the former Eastern bloc. Those pilgrimages took place between 1990 and 2003, which is right from the turn of 1989 till the end of the papal pontificate. Coming to the Slavic countries mentioned, the Pope recalled eleven names of writers that lived and worked in those countries from the 15th to the 20th century and quoted four of their works.
Keywords: Jan Paweł II, papież (1929-2005); narody słowiańskie; pielgrzymka; kultura